Effect of Two Different Haemostatic Agents on Microleakage in Subgingival Class II Restorations Restored with Flow Bulk-Fill Composite and Universal Restorative Composite by Co-curing Technique: An in vitro Study - Kondala, Niharika; Naga Lakshmi Reddy, Sampathi; Yalamanchi, Anusha; Upendranatha Reddy, Nagireddy; Sathish Kumar, Neshaneni; Meher Meenakshi, Chappidi (International Journal of Dental Materials, 2026)
Background: Microleakage at subgingival margins is a persistent challenge in composite restorations, particularly when gingival fluid and blood are contaminated. Haemostatic agents such as ferric sulfate and aluminium chloride are frequently used to control bleeding; however, their effects on marginal integrity and bonding remain controversial.Aim: To evaluate the effect of two different haemostatic agents—aluminium chloride and ferric sulfate—on microleakage in subgingival Class II restorations restored with flow bulk-fill and universal restorative composites using the co-curing technique.Materials and methods: Forty-five extracted human molars were divided into three groups (n=15 each): Group I: No haemostatic agent (control), Group II: Aluminium chloride (Ultradent Viscostat Clear), and Group III: Ferric sulfate (Ultradent Viscostat). Standardized Class II cavities were prepared 1.5 mm below the CEJ. After applying the respective agents, cavities were restored using a universal adhesive (3M ESPE Single Bond), flow bulk-fill composite (3M ESPE Filtek), and nano-hybrid composite (3M ESPE Filtek Z350 XT) via the co-curing technique. Samples were thermocycled, immersed in 2% methylene blue dye, and evaluated under a stereomicroscope (10×). Data were analysed using the Kruskal–Wallis test and the Mann–Whitney U test.Results: The control group exhibited the least microleakage, followed by the aluminium chloride group and ferric Sulfate group. Statistically significant differences (p < 0.05) were observed among the groups.Conclusion: Ferric sulfate significantly increased microleakage compared to aluminium chloride and control. Aluminium chloride demonstrated better compatibility with adhesive procedures. Thorough rinsing and drying of haemostatic residues are critical to achieve optimal bonding and reduce restoration failure.